2021
DOI: 10.1002/biof.1804
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D3 enhances the effects of omega‐3 oils against metabolic dysfunction‐associated fatty liver disease in rat

Abstract: This study investigated the effects of omega-3 oils (OM) and/or vitamin D 3 (VD) against metabolic dysfunction-associated fatty liver disease (MAFLD). Forty rats were divided into negative (NC) and positive (PC) controls, OM, VD, and OM + VD groups, and MAFLD was induced by high-fat/high-fructose diet (12 weeks). Oral OM (415 mg/kg/day) and/or intramuscular VD (290 IU/kg/ day) were given for 4 weeks (5 times/week). The PC animals were markedly obese and had hyperglycemia, insulin resistance, dyslipidemia, elev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 62 publications
3
5
0
Order By: Relevance
“…In accordance with a study by Refaat et al. ( 95 ), the present study demonstrated that VD increased the protein expression of PPARα in the liver. Accordingly, the protein expression of CPT1A was also increased after VD treatment.…”
Section: Discussionsupporting
confidence: 94%
“…In accordance with a study by Refaat et al. ( 95 ), the present study demonstrated that VD increased the protein expression of PPARα in the liver. Accordingly, the protein expression of CPT1A was also increased after VD treatment.…”
Section: Discussionsupporting
confidence: 94%
“…Cell apoptosis was detected in colonic tissues with a Click-iT™ Plus TUNEL Assay (#C10617; Thermo Fisher Scientific) and by following the manufacturer’s instructions. The co-detection of apoptotic bodies with cleaved Casp-3 was achieved by a sequential staining protocol, as described earlier ( 41 , 42 ). Briefly, anti-cleaved Casp-3 rabbit IgG monoclonal antibodies (#9661; Cell Signaling Technology Inc.) were added (1:400 concentration) for 3h following completion of the TUNEL protocol.…”
Section: Methodsmentioning
confidence: 99%
“…There was a reduction in the expression of SREBP-1c and its target genes, fatty acid synthase and acetyl CoA carboxylase, which demonstrated that vitamin D increased the production of antioxidant and anti-inflammatory chemicals. Simultaneously, it triggered the upregulation of hepatic mRNA expression of PPARα and CPT-1 and reduced leptin, induced adiponectin/AdipoR1 with suppression of the p53–p21 pathway of caspase-3/apoptosis, and increased SMP-30 levels [ 68 , 69 , 70 , 71 , 72 ].…”
Section: Discussionmentioning
confidence: 99%